Pre-commerce students perception towards online mathematic courses / Azlina Mohd Mydin ... [et al.] - Mohd Mydin, Azlina Mohd Mydin; Wan Mohammad, Wan Anisha; Abdul Wahab, Naemah; Abu Mansor, Siti Nurleena (Unit Penerbitan JSKM, 2021)
Online classes are the new trends in all our education system due to Pandamic COVID-19. To ensure that our education system does not lag behind, the ministry proposes to continue studies or schooling online. The student from pre university programme also are required to join the online classes although they are new to higher education center or university system. Pre-Commerce is one programme in PPT, UiTM that offers courses for those who did not preform well in SPM. Most of the student who joined these programme do not get good results in subjects like Mathematic and English. This research will study about the student perception towards online learning for mathematic course. An online survey has been conducted to study the student perspective and adaption for online classes especially for mathematic subject. The sample of this study are taken from Pre - Commerce student especially from UiTM Cawangan Pulau Pinang. In this study, we also elaborate the teaching methods used by the lecturer for teaching the mathematic course.